Swimming - Changing times - Goldsmith, W. (coachesinfo.com)
Today it is more and more difficult to get children for swimming. There is no doubt that with the increase in funding and focus given to high performance sport over the past ten years and the impact of sports science, coach education, recovery and training techniques that the elite end of the sport is looking fast and furious. But this represents about 1 percent of the sport. And if the other 99% isn`t going well, eventually, even this elite 1% will struggle. Numbers of registered swimmers are generally down around the world. That is a fact.